1990
DOI: 10.1002/tea.3660271010
|View full text |Cite
|
Sign up to set email alerts
|

The concept map as a research tool: Exploring conceptual change in biology

Abstract: This study examined the concurrent validity of concept maps as vehicles for documenting and exploring conceptual change in biology. Students (N = 91) who enrolled in an elementary science methods course were randomly assigned to one of two treatment groups. Subjects in both groups were administered a multiple‐choice/free‐response inventory which assayed their knowledge of “Life Zones in the Ocean,” and then were asked to construct a concept map on the same topic. Those in the experimental group subsequently re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
127
0
5

Year Published

1996
1996
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(133 citation statements)
references
References 11 publications
1
127
0
5
Order By: Relevance
“…Two of the studies (Markham et al, 1994;Wallace & Mintzes, 1990) supported the concurrent validity of concept maps as vehicles for documenting and exploring conceptual change in biology. Two others (Laturno, 1994;Park, 1993) used concept maps in studies pertaining to mathematics.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Two of the studies (Markham et al, 1994;Wallace & Mintzes, 1990) supported the concurrent validity of concept maps as vehicles for documenting and exploring conceptual change in biology. Two others (Laturno, 1994;Park, 1993) used concept maps in studies pertaining to mathematics.…”
mentioning
confidence: 90%
“…Six recent studies have used concept maps to assess cognitive structure or conceptual understanding (Beyerbach, 1986;Coleman, 1993;Laturno, 1994;Markham, Mintzes, & Jones, 1994;Park, 1993;Wallace & Mintzes, 1990). Two of the studies (Markham et al, 1994;Wallace & Mintzes, 1990) supported the concurrent validity of concept maps as vehicles for documenting and exploring conceptual change in biology.…”
mentioning
confidence: 99%
“…These maps mostly adopt a hierarchical structure in which subtopics or highly specific concepts are connected to a broad, all-encompassing concept. Many studies have identified several applications of concept maps, such as assessment devices (Wallace and Mintzes, 1990;Walker and King, 2002;Besterfield-Sacre et al, 2003) and planning tools (Ruiz-Primo and Shavelson, 1996;Starr and Krajcik, 1990;Posner and Rudnitsky, 2000). Moreover, concept maps are widely used by instructional designers, engineers, technical writers, and others to organise and structure knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, concept maps have been used to assess changes in student conceptual understanding. In their seminal study, Wallace and Mintzes observed that students' concept maps were substantially different in complexity and structure of the knowledge base from the pre-test to the post-test [29]. This led the researchers to conclude that concept mapping is a valid tool to document students' changes in conceptual understanding.…”
Section: Vocabulary Development and Stem Achievementmentioning
confidence: 99%